Electronic communication techniques and their role in supporting the academic activities of university faculty members: An applied study piloted on the lecturers of Lebenese French University - Jawad Mohammed Ameen issa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Usage of internet and ways to benefit from it in the field of scientific research and academic communication has become a necessity to keep pace with scientific and learning development by faculty members. The university need to provide a conducive environment for staff members to tap in to the technology for the purpose of developing their capacities in this field. The faculty members need to improve their capacities and skills to use the Internet technology in order to know and understand the latest developments in their specializations, whether in the areas of research or teaching. Therefore, most universities and institutions in the higher education in most of the countries throughout the world are connected to Internet, and many studies have indicated that universities are giving their faculty members opportunities to use the Internet and benefit from it for learning and research purposes. The objective of this study is to identify the various approaches of electronic communication and its role in supporting the academic activities of university lecturers. This study relied on the survey methodology. The study also used the survey methodology to get an insight into the scientific monitoring and the patterns and also the motives of university Lectures to use the electronic communication techniques. The sample focused on (50) respondents from the Lebanese French University male and female lecturer. We were selective in terms of the sample which was consisted of the faculty members at the Lebanese French University so they can express fair opinion on the reality of the academic work inside the university. The most significant results of the study is that the majority of respondents replied in the survey that they use the Internet as a source of research and academic information, the study demonstrated that most faculty members of both genders considered the Internet as a good source for achieving information.